“It looks like my die has a favorite number”—maker education for 21st century skills in primary science education - Krebs, Ann-Katrin (Frontiers in Education, 2026)
This paper explores the integration of Maker Education into primary schools and its potential to foster essential digital and interdisciplinary skills. Grounded in constructivist and constructionist theories, Maker Education emphasizes hands-on, project-based learning using traditional and digital tools, particularly 3D design and printing, enabling learners to actively design, build, and iterate their own. The paper draws on practical examples from German-speaking countries, including a detailed classroom project in which primary students used TinkerCAD to design and analyze 3D-printed dice. The implementations are characterized by flexible, open-ended learning environments that support inquiry-based and collaborative learning, even with limited resources. The examined cases indicate positive effects on student motivation, engagement, and competence development. Students developed skills in geometry, mass distribution, digital fabrication, and scientific inquiry, particularly when learning activities were connected to real-world problems and collaborative making. Maker Education supports the development of 21st-century competencies such as creativity, critical thinking, communication, and digital literacy. However, its sustainable implementation requires addressing curricular constraints, technical demands, and the need for systematic integration of maker pedagogies into teacher education.